Business models and investment options for use of licensed shared access of spectrum - Jan Markendahl; Ashraf Awadelakrim Widaa Ahmed; Bengt G. Mölleryd (International Telecommunications Society (ITS), 2013)
A Licensed Shared Access (LSA) authorization/license includes an agreement between the secondary sharing user (some type of operator) and the primary license holder (e.g. a government organization) around the conditions of use (where, when, how). Compared to secondary access LSA offers a more attractive case for long term investments. The contribution in this paper is that we look into how LSA can be used by different types of actors. The outcome depends heavily on what type of actor that makes use of the spectrum using LSA. Based on cost structure analysis (leading to required investments) and analysis of availability of the basic spectrum resource we can identify clear differences of the commercial usability of spectrum awarded using LSA, all depending on what actors that make use of the LSA contract. Cases where new actors need to invest a lot in new infrastructure do not that look that promising. We cannot identify a separate LSA business case that is feasible from a business perspective (where the key resource for the operator is spectrum awarded using LSA). Service availability that cannot be guaranteed due to LSA type of spectrum being the only resource seems risky, especially when combined with high investments. However this applies only for outdoor deployment. For deployment of a new indoor network the situation is different. The cost structure is the same no matter if a new or existing actor deploys the networks. In addition, a multitude of spectrum bands and spectrum access options exist indoor so the service provisioning will be less vulnerable if some part of spectrum is not available some period of time.
Keywords: 330; Actors; Competition; Cost structure analysis; Licensed/non-licensed spectrum bands; Mobile broadband; Network deployment; Regulation; Secondary/shared spectrum access